Degendering Leadership in Higher Education - Katuna, Barret (Great debates in higher education., 2019)
Through 34 interviews with women and men serving as presidents, deans, and provosts at some of the United States' top colleges and universities, this book explores what degendered leadership looks like in an academic setting and creates a path for inspired, talented, and qualified leadership that is not reduced to gender norms and stereotypes.